1O100, 000 genomes project: Integrating whole genome sequencing (WGS) data into clinical practice. (7th November 2019) - Sosinsky, A; Ambrose, J; Zarowiecki, M; Mitchell, J; Henderson, S; Murugaesu, N; Hamblin, A; Turnbull, C; Walker, S; Perez-Gil, D; Rueda-Martin, A; Fowler, T; et al.
Abstract: Background: The 100, 000 Genomes Project aims to improve cancer care for NHS patients in the UK through personalised medicine. Our target is to return WGS results to clinicians in a clinically meaningful timescale to facilitate diagnosis and treatment choices for patients, and in parallel to provide a research platform of genomic data linked to longitudinal clinical data. Methods: We present here an overview of clinical utility for reported outcomes. To date, bioinformatics reports for WGS, with links to potentially relevant therapies and UK clinical trials, have been produced for more than 14, 000 cancer patients in the UK Currently our bioinformatics analysis of WGS includes clinical interpretation of somatic small variants, somatic structural and copy number variants (SV/CNV), germline pertinent findings, mutational burden and signatures. To iteratively develop a high-quality bioinformatics pipeline and to monitor clinical utility of returned results, we are collecting feedback via the 100, 000 Genomes Project Interpretation Portal from NHS Molecular Tumour Boards. These data suggest that WGS has the potential to affect patient management. Future applications will include the utilisation of pan-genomic markers to better stratify patients within the context of a clinical study. Results: WGS has the ability to replace multiple standard of care tests as it has the potential to detect all types of variants (SV/CNV/SNV/indels) as well as emerging pan-genome biomarkers in a single test. In this study we use samples submitted as part of the 100, 000 Genomes Project to investigate the feasibility of WGS as an alternative to conventional testing. Overall comparison of WGS with the results of NGS panels (96 patients, 156 clinically-relevant SNVs), high-depth exome sequencing (10 patients, 3150 SNVs, 140 indels), cytogenetic FISH tests (70 patients, 259 SVs, 100 CNVs), immunohistochemistry tests for Mismatch Repair Deficiency (265 patients) and HER2 status (154 patients) demonstrated Positive Percentage Agreement > 90% and False Positive Rate < 5%. Conclusions: Further work is required to validate fully all aspects of the WGS analysis pipeline but these results indicate that WGS can reliably detect clinically relevant biomarkers in the genomes of cancer patients. Legal entity responsible for the study: Genomics England. Funding: Genomics England. Disclosure: All authors have declared no conflicts of interest.